Design, Implementation, Monitoring, and Sharing of Performance Standards for Laboratory Animal Use: Summary of a Workshop - National Academies of Sciences, Engineering,; Medicine
In order to better understand the critical issues pertaining to the concept of performance standards for laboratory animal use, the Institute for Laboratory Animal Research Roundtable on Science and Welfare in Laboratory Animal Use held a public workshop on April 20-21, 2015. The purpose of the workshop was to promote the appropriate and responsible care of animals in research, to provide a balanced and civil forum for discussion and collaboration, and to help build transparency and trust among stakeholders. Participants addressed the challenges of defining, developing, implementing, assessing, and validating performance standards to ensure \

Biosecurity Challenges of the Global Expansion of High-Containment Biological Laboratories: Summary of a Workshop - National Academy of Sciences; National Research Council (The National Academies Press, 2012)
During July 10-13, 2011, 68 participants from 32 countries gathered in Istanbul, Turkey for a workshop organized by the United States National Research Council on Anticipating Biosecurity Challenges of the Global Expansion of High-containment Biological Laboratories. The United States Department of State's Biosecurity Engagement Program sponsored the workshop, which was held in partnership with the Turkish Academy of Sciences. The international workshop examined biosafety and biosecurity issues related to the design, construction, maintenance, and operation of high-containment biological laboratories- equivalent to United States Centers for Disease Control and Prevention biological safety level 3 or 4 labs. Although these laboratories are needed to characterize highly dangerous human and animal pathogens, assist in disease surveillance, and produce vaccines, they are complex systems with inherent risks. Biosecurity Challenges of the Global Expansion of High-Containment Biological Laboratories summarizes the workshop discussion, which included the following topics: Technological options to meet diagnostic, research, and other goals; Laboratory construction and commissioning; Operational maintenance to provide sustainable capabilities, safety, and security; and Measures for encouraging a culture of responsible conduct. Workshop attendees described the history and current challenges they face in their individual laboratories. Speakers recounted steps they were taking to improve safety and security, from running training programs to implementing a variety of personnel reliability measures. Many also spoke about physical security, access controls, and monitoring pathogen inventories. Workshop participants also identified tensions in the field and suggested possible areas for action.

Strengthening the Disaster Resilience of the Academic Biomedical Research Community: Protecting the Nation's Investment - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
The academic biomedical research community is a hub of employment, economic productivity, and scientific progress. Academic research institutions are drivers of economic development in their local and state economies and, by extension, the national economy. Beyond the economic input that the academic biomedical research community both receives and provides, it generates knowledge that in turn affects society in myriad ways. The United States has experienced and continues to face the threat of disasters, and, like all entities, the academic biomedical research community can be affected. Recent disasters, from hurricanes to cyber-attacks, and their consequences have shown that the investments of the federal government and of the many other entities that sponsor academic research are not uniformly secure. First and foremost, events that damage biomedical laboratories and the institutions that house them can have impacts on the safety and well-being of humans and research animals. Furthermore, disasters can affect career trajectories, scientific progress, and financial stability at the individual and institutional levels. Strengthening the Disaster Resilience of the Academic Biomedical Research Community offers recommendations and guidance to enhance the disaster resilience of the academic biomedical research community, with a special focus on the potential actions researchers, academic research institutions, and research sponsors can take to mitigate the impact of future disasters.

Safe Science: Promoting a Culture of Safety in Academic Chemical Research - National Research Council (The National Academies Press, 2014)
Recent serious and sometimes fatal accidents in chemical research laboratories at United States universities have driven government agencies, professional societies, industries, and universities themselves to examine the culture of safety in research laboratories. These incidents have triggered a broader discussion of how serious incidents can be prevented in the future and how best to train researchers and emergency personnel to respond appropriately when incidents do occur. As the priority placed on safety increases, many institutions have expressed a desire to go beyond simple compliance with regulations to work toward fostering a strong, positive safety culture: affirming a constant commitment to safety throughout their institutions, while integrating safety as an essential element in the daily work of laboratory researchers. Safe Science takes on this challenge. This report examines the culture of safety in research institutions and makes recommendations for university leadership, laboratory researchers, and environmental health and safety professionals to support safety as a core value of their institutions. The report discusses ways to fulfill that commitment through prioritizing funding for safety equipment and training, as well as making safety an ongoing operational priority. A strong, positive safety culture arises not because of a set of rules but because of a constant commitment to safety throughout an organization. Such a culture supports the free exchange of safety information, emphasizes learning and improvement, and assigns greater importance to solving problems than to placing blame. High importance is assigned to safety at all times, not just when it is convenient or does not threaten personal or institutional productivity goals. Safe Science will be a guide to make the changes needed at all levels to protect students, researchers, and staff.

Transportation of Laboratory Animals: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
The obligation to treat animals used in research ethically and humanely extends beyond their lives in the laboratory to include their transportation from place to place. Yet transporting animals is a highly regulated and complex process that raises many difficult issues. To examine these issues, the Roundtable on Science and Welfare in Laboratory Animal Use held a workshop on September 3-4, 2014, in Washington, DC. More than 200 people participated in the workshop in person and online, including representatives of academic research institutions, pharmaceutical and consumer product companies, government agencies, research advocacy groups, professional associations, and the public. The workshop was designed to draw attention to the essential thoughtful journey planning behind each transport of laboratory animals.

Protecting the Frontline in Biodefense Research: The Special Immunizations Program - National Research Council (The National Academies Press, 2011)
The U.S. Army's Special Immunizations Program is an important component of an overall biosafety program for laboratory workers at risk of exposure to hazardous pathogens. The program provides immunizations to scientists, laboratory technicians and other support staff who work with certain hazardous pathogens and toxins. Although first established to serve military personnel, the program was expanded through a cost-sharing agreement in 2004 to include other government and civilian workers, reflecting the expansion in biodefense research in recent years. Protecting the Frontline in Biodefense Research examines issues related to the expansion of the Special Immunizations Program, considering the regulatory frameworks under which the vaccines are administered, how additional vaccines might be considered for inclusion in the Program, and factors that might influence the development and manufacturing of vaccines for the Special Immunizations Program.

Indo-U.S. Workshop on Challenges of Emerging Infections and Global Health Safety: Summary of a Workshop - National Academy of Sciences (The National Academies Press, 2016)
The United States and India have pledged to deepen the linkages between their people, their businesses, and their governments for the mutual benefit of both countries and for the promotion of global peace, stability, economic growth and prosperity. Both nations are now inclined to improve relations and cooperation, but the nations need specific actions that will yield progress and build confidence and momentum for further cooperation. The Indo-U.S. Workshop on Challenges of Emerging Infections and Global Health Safety, held in November 2014, encouraged scientists from both countries to examine global issues related to emerging and existing infections and global health safety, to share experience and approaches, and to identify opportunities for cooperation to improve practice and research in these areas. This report summarizes the presentations and discussions from the workshop.

Reusability of Facemasks During an Influenza Pandemic: Facing the Flu - Institute of Medicine (The National Academies Press, 2006)
Any strategy to cope with an influenza pandemic must be based on the knowledge and tools that are available at the time an epidemic may occur. In the near term, when we lack an adequate supply of vaccine and antiviral medication, strategies that rely on social distancing and physical barriers will be relatively more prominent as means to prevent spread of disease. The use of respirators and facemasks is one key part of a larger strategy to establish barriers and increase distance between infected and uninfected individuals. Respirators and facemasks may have a role in both clinical care and community settings. Reusability of Facemasks During an Influenza Pandemic: Facing the Flu answers a specific question about the role of respirators and facemasks to reduce the spread of flu: Can respirators and facemasks that are designed to be disposable be reused safely and effectively? The committee2014assisted by outstanding staff2014worked intensively to review the pertinent literature; consult with manufacturers, researchers, and medical specialists; and apply their expert judgment. This report offers findings and recommendations based on the evidence, pointing to actions that are appropriate now and to lines of research that can better inform future decisions.

Chemical Laboratory Safety and Security: A Guide to Developing Standard Operating Procedures - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
The U.S. Department of State charged the Academies with the task of producing a protocol for development of standard operating procedures (SOPs) that would serve as a complement to the Chemical Laboratory Safety and Security: A Guide to Prudent Chemical Management and be included with the other materials in the 2010 toolkit. To accomplish this task, a committee with experience and knowledge in good chemical safety and security practices in academic and industrial laboratories with awareness of international standards and regulations was formed. The hope is that this toolkit expansion product will enhance the use of the previous reference book and the accompanying toolkit, especially in developing countries where safety resources are scarce and experience of operators and end-users may be limited.

Prudent Practices in the Laboratory: Handling and Management of Chemical Hazards, Updated Version - National Research Council (The National Academies Press, 2011)
Prudent Practices in the Laboratory2014the book that has served for decades as the standard for chemical laboratory safety practice2014now features updates and new topics. This revised edition has an expanded chapter on chemical management and delves into new areas, such as nanotechnology, laboratory security, and emergency planning. Developed by experts from academia and industry, with specialties in such areas as chemical sciences, pollution prevention, and laboratory safety, Prudent Practices in the Laboratory provides guidance on planning procedures for the handling, storage, and disposal of chemicals. The book offers prudent practices designed to promote safety and includes practical information on assessing hazards, managing chemicals, disposing of wastes, and more. Prudent Practices in the Laboratory will continue to serve as the leading source of chemical safety guidelines for people working with laboratory chemicals: research chemists, technicians, safety officers, educators, and students.

Occupational Health and Safety in the Care and Use of Research Animals - National Research Council (The National Academies Press, 1997)
Much has been written about the care of research animals. Yet little guidance has appeared on protecting the health and safety of the people who care for or use these animals. This book, an implementation handbook and companion to Guide For the Care and Use of Laboratory Animals, identifies principles for building a program and discusses the accountability of institutional leaders, managers, and employees for a program's success. It provides a detailed description of risks2014physical and chemical hazards, allergens and zoonoses, and hazards from experiments2014which will serve as a continuing reference for the laboratory. The book offers specific recommendations for controlling risk through administrative procedures, facility design, engineering controls, and periodic evaluations. The volume focuses on the worker, with detailed discussions of work practices, the use of personal protective gear, and the development of an emergency response plan. This handbook will be invaluable to administrators, researchers, and employees in any animal research facility. It will also be of interest to personnel in zoos, animal shelters, and veterinary facilities.

Evaluation of the Health and Safety Risks of the New USAMRIID High-Containment Facilities at Fort Detrick, Maryland - National Research Council (The National Academies Press, 2010)
The U.S. Army Medical Research Institute of Infectious Diseases in Frederick, Maryland, is designed to handle pathogens that cause serious or potentially lethal diseases, which require the research performed on them be contained to specialized laboratories. In 2007 a decision was made to expand those facilities causing concern among area residents that public health and safety risks, and strategies to mitigate those concerns were not adequately considered in the decision to go forward with the expansion. In Evaluation of the Health and Safety Risks of the New USAMRIID High Containment Facilities at Fort Detrick, Maryland a group of experts in areas including biosafety, infectious diseases, industrial hygiene, environmental engineering, risk assessment and epidemiology, explored whether measures were being taken to ensure prevention and mitigation of risk to the health and safety of workers and the public. They also assessed whether the procedures and regulations employed meet accepted standards of the Centers for Disease Control and Prevention and the National Institutes of Health. Evaluation of the Health and Safety Risks of the New USAMRIID High Containment Facilities at Fort Detrick, Maryland evaluates the health and safety aspects of the environmental impact statement developed to support the construction of the new laboratories and explores the institute's operating requirements, medical and emergency management response plans and communication and cooperation with the public. The book recommends that USAMRIID continue to set high standards for advancing security, operational, and biosurety measures, and that additional measures be taken to provide assurance that experienced medical professionals are readily available to consult on unusual infectious diseases. It also suggests that USAMRIID expand its two-way communications with the public.

Guide for the Care and Use of Laboratory Animals: Eighth Edition - National Research Council (The National Academies Press, 2011)
A respected resource for decades, the Guide for the Care and Use of Laboratory Animals has been updated by a committee of experts, taking into consideration input from the scientific and laboratory animal communities and the public at large. The Guide incorporates new scientific information on common laboratory animals, including aquatic species, and includes extensive references. It is organized around major components of animal use: Key concepts of animal care and use. The Guide sets the framework for the humane care and use of laboratory animals. Animal care and use program. The Guide discusses the concept of a broad Program of Animal Care and Use, including roles and responsibilities of the Institutional Official, Attending Veterinarian and the Institutional Animal Care and Use Committee. Animal environment, husbandry, and management. A chapter on this topic is now divided into sections on terrestrial and aquatic animals and provides recommendations for housing and environment, husbandry, behavioral and population management, and more. Veterinary care. The Guide discusses veterinary care and the responsibilities of the Attending Veterinarian. It includes recommendations on animal procurement and transportation, preventive medicine (including animal biosecurity), and clinical care and management. The Guide addresses distress and pain recognition and relief, and issues surrounding euthanasia. Physical plant. The Guide identifies design issues, providing construction guidelines for functional areas; considerations such as drainage, vibration and noise control, and environmental monitoring; and specialized facilities for animal housing and research needs. The Guide for the Care and Use of Laboratory Animals provides a framework for the judgments required in the management of animal facilities. This updated and expanded resource of proven value will be important to scientists and researchers, veterinarians, animal care personnel, facilities managers, institutional administrators, policy makers involved in research issues, and animal welfare advocates.